How to reach compromises in life satisfaction: a conflicting and multidimensional task - Oliveira Henriques, Carla; Marcenaro-Gutiérrez, Óscar David; López-Agudo, Luis Alejandro; Luque-Gallego, Mariano (My University, 2019)
Recent concerns around the importance of job and life satisfaction on firms’ productivity have been brought to the policy debate in the European Union. Irrespective of the numerous scientific publications that have been studying the main determinants of workers’ life satisfaction, a gap remains on how to grasp compromises between these. The importance of finding such compromises can be particularly relevant, in face of the multiple factors, seldom intertwined and at the same time conflicting, which have a well-known influence on workers’ well-being. Therefore, policymakers should be supported with sound methodological tools to help them shape policies that will further promote workers’ life satisfaction. With this reasoning in mind, we have developed a multiobjective interval programming model through the use of econometric techniques, where four different workers’ life satisfaction determinants (i.e. satisfaction with education, present work, family life and social life) are viewed as objective functions. Furthermore, we have made a separate assessment of the factors that have an influence on life satisfaction for both genders, because of the discrepancies that might arise with this regard. Overall, we were able to conclude that female workers usually have to devote more time to their work than men to get the highest levels of satisfaction regardless of the features under evaluation. Additionally, having one child is sufficient to obtain the highest levels of well-being both for female and male workers. One of the possible implications of these findings is that the existing work-family priorities are clearly not in line with the current falling birth rates all over Europe. Thus, new supportive workplace policies should be in place that could change people’s priorities regarding their work and family life.
Keywords: Econometría; Life satisfaction; Work and family life; Multiobjective interval programming; Econometric analysis